White spot syndrome virus (WSSV) infection impacts intestinal microbiota composition and function in Litopenaeus vannamei. Issue 84 (January 2019) - Wang, Jun; Huang, Youjia; Xu, Kaihang; Zhang, Xiaoyong; Sun, Hongyan; Fan, Lanfen; Yan, Muting
Abstract: Intestinal microbiota homeostasis is crucial to the health of host. Pathogen invasion results in dynamics of microbiota composition and structure, disrupting their function in maintaining host health. WSSV is the most prevalent viral pathogen and is able to cause extremely high mortality in Litopenaeus vannamei . However, the changes of intestinal microbiota induced by WSSV are yet to be elucidated. In this study, we analyzed and compared the microbiota of healthy and WSSV-challenged shrimp intestines. Though the richness and diversity of microbiota was barely affected by WSSV, the abundance of predominant phyla like Proteobacteria and Fusobacteria were upregulated significantly, while Bacteroidetes and Tenericutes were significantly decreased in WSSV-infected shrimps. At the genus level, significant increase was observed in Photobacterium, Propionigenium and Arcobacter, as well as significant decrease in Candidatus Bacilloplasma and Flavobacterium in WSSV-infected shrimps. Additionally, metagenomic predictions by PICRUSt suggested that the altered microbiota was mainly related to metabolism, human diseases, genetic information processing, environmental information processing and cellular processes. These results suggested that the invasion of WSSV could impact intestinal microbiota composition and function in L. vannamei . Highlights: WSSV infection impacts intestinal microbiota composition in Litopenaeus vannamei. WSSV upregulated the abundance of phyla Proteobacteria and Fusobacteria significantly. Phyla Bacteroidetes and Tenericutes decreased significantly after WSSV infection. WSSV changed abundance of some pathogenic bacteria within genus Arcobacter and Flavobacterium. Predicted KEGG pathways related to metabolism and biological processes were altered by WSSV.